Efficient and stable low-temperature CO oxidation over Pt/In–SnO2 composite triggered by abundant oxygen vacancies and adsorption sites. Issue 11 (26th April 2021) - Sun, Yukun; Gao, Yang; He, Chi; Song, Weiyu; Jiang, Zeyu; Albilali, Reem; Bai, Bo
Abstract : In ion doping can greatly improve the active oxygen migration ability in the Pt/In–SnO2 catalyst, which is beneficial to CO oxidation at low temperature. Abstract : It is of great significance to design highly active and stable catalysts for CO oxidation. Herein, a Pt/In–SnO2 catalyst was firstly fabricated via a facile hydrothermal reaction coupled with photoreduction strategy, achieving 1 vol% of CO totally oxidized at just 145 °C, over 200 °C lower than that of Pt/SnO2 . Moreover, Pt/In–SnO2 demonstrates superior catalytic stability and recyclability under both dry and humid conditions. Incorporation of In cations results in marked structure distortion of SnO2, promoting the formation of oxygen vacancies and enhancing the concentration and mobility of reactive oxygen species. Abundant Pt sites over Pt/In–SnO2 further accelerate CO adsorption and activation. Density functional theory results prove that the energy barrier of CO oxidation reduces from 0.85 to 0.75 eV after In doping and the produced CO2 can desorb spontaneously from the catalyst surface, which accelerates the CO oxidation process. This work provides new ideas for designing robust catalysts for low-temperature CO elimination.